Foot and ankle pain and risk of incident knee osteoarthritis and knee pain: data from the Multicentre Osteoarthritis Study - Perry, TA; Segal, NA; Bowen, C; Gates, L; Arden, N; Nevitt, MC (Elsevier, 2021)
Objectives To examine whether foot and/or ankle pain increases the risk of knee OA.